RELIGIUSITAS, KESADARAN HALAL, DAN KEPERCAYAAN PRODUK DALAM MEMBENTUK KEPUTUSAN PEMBELIAN - Anggun Oktaviani; Andi Azhar (UM. Bengkulu, 2026)
This study aims to analyze the influence of religiosity and halal awareness on halal cosmetic purchase decisions through the mediation of product trust in 385 Muslim consumers in Bengkulu. The type of quantitative research with the Partial Least Square Structural Equation Modeling (PLS-SEM) approach using SmartPLS 4.0, primary data was obtained through online and face-to-face questionnaires with purposive sampling, bootstrapping analysis of 5000 subsamples for hypothesis test at a significance level of α=0.05. The results showed that all hypotheses were significantly accepted (p<0.001, T-statistic>3.80) with religiosity having a significant positive effect directly on purchase decisions with a value of β=0.253 T=3.80, halal awareness of purchase decisions with a value of β=0.288 T=4.10, strong lines of product trust in purchase decisions with a value of β=0.484 T=7.20, the dominant effect of indirect religiosity through product trust with a value of β=0.17 T=3.50 and halal awareness indirectly through product trust with a value of β=0.20 T=4.02. Robust structural model with R² purchase decision 56% (substantial), AVE>0.70, composite reliability >0.90, meets convergent/discriminant validity and reliability. Keywords: religiosity, halal awareness, product trust, purchase decision.